Policing The Drunk Driving Problem: A Longitudinal Examination of DUI Enforcement and Alcohol Related Crashes in the U.S. (1985–2015) - Stringer, Richard J. (American journal of criminal justice, 2019)
This project examines the relationship between police enforcement of driving under the influence (DUI) and fatal alcohol related crashes. This article merged data from several sources to fit several 3-level growth curve models that assess the relationship between DUI arrests and fatal alcohol related crashes in U.S. counties from 1985 to 2015. The findings indicate that increases in DUI arrests are related to decreased fatal alcohol related crashes during the period. However, the two are not linearly related and the relationship varies across states. The non-linearity indicates there is a point of diminished returns where increased arrests are no longer related to reductions in fatalities. These findings suggest that policy makers should explore alternative methods of reducing crashes to supplement enforcement efforts such as addressing problems of alcoholism and traffic safety.